1982
DOI: 10.5962/bhl.title.105629
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and environmental effects on fatty acid composition, iodine value and oil content of peanut (Arachis hypogaea L.) /

Abstract: of the supervisory committee, for his invaluable help in the analysis of the data, as well as for his suggestions to improve the manuscript. The author also expresses appreciation to the Brazilian Agency for Agricultural Research (EI4BRAPA) for the financial support given during the graduate program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Holaday & Pearson (1974) found that higher temperature during the last 4 weeks before harvest resulted in higher oleic acid and lower linoleic acid content. Bovi (1982), Raheja et al (1987) and Önemli (2012) observed that the correlation between oleic acid and linoleic acid percentages was negative in peanut oil. Several factors affect the fatty acid content in peanut oil, including variety, seasonal variation, genotype, location, air and soil temperature, planting date, soil nutrient, moisture availability, growing conditions and maturity (Young & Worthington, 1974;Brown et al, 1975;How & Young, 1983;Hashim et al, 1993;Hassan et al, 2005;Hassan & Ahmed, 2012;Chaiyadee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Holaday & Pearson (1974) found that higher temperature during the last 4 weeks before harvest resulted in higher oleic acid and lower linoleic acid content. Bovi (1982), Raheja et al (1987) and Önemli (2012) observed that the correlation between oleic acid and linoleic acid percentages was negative in peanut oil. Several factors affect the fatty acid content in peanut oil, including variety, seasonal variation, genotype, location, air and soil temperature, planting date, soil nutrient, moisture availability, growing conditions and maturity (Young & Worthington, 1974;Brown et al, 1975;How & Young, 1983;Hashim et al, 1993;Hassan et al, 2005;Hassan & Ahmed, 2012;Chaiyadee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the average oil content of peanut varieties was found higher in main cropped than in double cropped growing season. In different studies by Holaday & Pearson (1974), Brown et al (1975), Raheja et al (1987), Hassan et al (2005), Yav et al (2008) and Isleib et al (2008) were reported that the oil percentage of peanut kernel varies between 35 to 56% depending on genotype and growing conditions, and the oil content of peanut varieties influence by genotype, seed maturity, climatic conditions, geographical location, growing season and growing conditions. Similar results were reported by various researchers (Özcan & Seven, 2003;Yav et al, 2008;Hassan & Ahmed, 2012;Önemli, 2012;Chowdhury et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations